IDENTIFIKASI GEN / QTL (Quantitative Trait Loci) SIFAT TOLERAN CEKAMAN ALUMINIUM PADA GALUR-GALUR PADI GOGO - Dwinita Wikan Utami; I Rosdianti; S Yuriyah; AD Ambarwati; I Hanarida; Suwarno Suwarno; Miftahudin Miftahudin (BERITA BIOLOGI, 2016)
Program on the ability of agriculture to provide rice as a staple food tends to decrease with the reduced land area used for rice cultivation. improvement rice production should be directed to use  marginal land  as dry and acid land, where poisoning aluminium was seen as a constrain factor. Development of Aluminium (Al) tolerant variety is needed to increase rice production. This technology was environmentally friendly, cheaper and also easier for farmers adopted. The rice lines with broad genetics background which tolerant to Al toxicity has been produced by breeding program. The diversity of Indonesian local rice germplasm is a basic foundation on development of Al toxicity tolerant rice varieties. The purpose of this research was to analyze the genotype variety using 384 SNPs markers on selected Al tolerant rice lines based on bioinformatics approach. Based on the 384 SNPs markers, the total 26 selected  genotypes were clustered into 5 groups. Each group was having varied Relative Root Length (RRL), which was an Al tolerant parameter of phenotype. These groups were indicated for having different genes or QTL that were related to the Al tolerant character. The association analysis obtained 9 significant SNPs markers that can be applied as the molecular markers for assisting selection in breeding  program.